Возрождение традиции - Секерская, Н.М. (Материалы по археологии Северного Причерноморья, 2009)
Тhis information is about the history of creation the collected articles «Materials on the Northem Black Sea Basin Archaeology». The first volume of the periodical was puЬlished in 1957 and was being issued until 1976 with interruptions. Those collected articles included the studies and reports on materials of archaeological investigations on monuments of Paleolithic, Mesolithic, Copper and Bronze Age, Antique epoch and the Middle Ages. The majority of these works have not lost actuality until now. It is necessary for museum to have its own periodical in connection with its scientific activity. The resumed collected articles «Materials on the Northem Black .Sea Basin Archaeology» will Ье such puЫication beginning from the 9th issue.